Jigoku dalam Komik Hoozuki No Reitetsu Karya Natsumi Eguchi - Alit Anggarani Apsari, Anak Agung (Humanis; Vol 22 No 1 (2018), 2018)
This research, entitled “Jigoku in Hoozuki No Reitetsu Comic by Natsumi Eguchi”, analyzed the image of hell (Jigoku) in a comic entitled Hoozuki No Reitetsu. This study used liguistic anthropology theory and semiotic theory by Marcel Danesi. The result of the research is that there are so many kinds of Jigoku with different way of images. Hell is described as a spot to torture sinners after death based on buddhism. There are fifteen layers of hell based on the comic. Meanwhile the real purpose of Hoozuki No Reitetsu comic for the citizen of Japan is for entertainment, central of information, and for reflection of one's self.